The Influence of Environmental Conditions on the Design of Nuwo Sesat, the Traditional House of Lampung - Rafli Alhaqi Anhuma Turaya (CV. Gio Architect, 2026)
This study aims to identify and analyze the influence of environmental factors on the design elements of Nuwo Sesat, the traditional house of Lampung Province. The research focuses on the interaction between natural environmental conditions such as the humid tropical climate, topography, and potential natural hazards and the architectural elements of Nuwo Sesat. Data were collected through direct observation, physical documentation, interviews with customary elders, and environmental measurements across several Nuwo Sesat samples in Bandar Lampung and West Tulang Bawang. The results reveal a significant correlation between stilt structures, roof forms, building orientation, ventilation systems, and material selection with adaptive responses to high rainfall, temperature, humidity, and local soil conditions. This study formulates a set of adaptive design principles grounded in local wisdom that can be applied to contemporary architecture. The findings are significant not only for the preservation of cultural heritage but also for the development of architecture that is responsive to local environmental conditions.